Business research methods / Alan Bryman; Emma Bell; Bill Harley - Bryman, Alan
"Business Research Methods is the complete introduction to doing business research and is an ideal guide for students embarking on a research project. Developed specifically with business and management students in mind, this textbook explores the nature and purpose of business research and the issues it entails, while also providing students with practical advice through 'Tips and skills' boxes. In addition to a broad range of relevant examples, the book features a substantial discussion of ethics, and a strong emphasis on the most frequent challenges faced by students, such as choosing a research question, planning a project, and writing it up.Fresh voices and perspectives run throughout this edition. New author, Bill Harley, further internationalizes the book's coverage, based on his expertise in the Australian business and management context. Also hear from Amrit, Jordan, Anna, Ed, and Alex - an additional five students whose personal insights and advice in the 'student experience' feature help you avoid common mistakes, and follow their successful strategies when undertaking your own research project.New to this EditionAn additional five students provide first-hand accounts of their experience of doing business research, with accompanying videos available onlineExtended material on 'ethics creep', 'big data', and writing academicallyE-Research is now woven throughout the text, better reflecting how internet research methodology is taughtA new test bank and new discussion questions for lecturers are available as part of the educator-only online resourcesThis edition has been extensively streamlined to provide even more focused coverage of the key areas of business researchJargon has been simplified throughout and clear, full explanations of methodologies and philosophies are providedThis title is available as an eBook. Please contact your Sales and Learning Resource Consultant for more information." -- Provided by publisher.